THE ANALYSIS OF FIGURATIVE LANGUAGE IN SONG LYRIC BY INDINA MENZEL - Fachri Yunanda; Yossy Kevin Parulian Pardede; Novia Esra Wati; Angelika Sara Deaparin; Aprilia Eka Krisdayanti Tafonao (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2021)
In writing songs, songwriters often use figurative language. In this study, the researchers analyzed the figurative language contained in three of Idina Menzel's songs, namely